Should Minor Stroke Patients Be Thrombolyzed? A Focused Review and Future Directions. Issue 3 (April 2015) - Yu, Amy Y. X.; Hill, Michael D.; Coutts, Shelagh B.
Stroke is a leading cause of morbidity and mortality worldwide. Up to 80% of ischemic stroke patients may initially present with minor symptoms. Minor stroke and transient ischemic attack patients are typically treated conservatively with antiplatelet agents and general vascular prevention strategies. Yet a high proportion develop recurrent stroke or progression of stroke and up to one in four of these patients are disabled or dead at follow-up. Minor or rapidly improving symptoms are the top reasons for withholding thrombolytic therapy to time-eligible stroke patients as they are believed to be 'too good to treat'. The benefits and risks of treating mild ischemic strokes are still unclear. The increasing use of computed tomography angiography and its ability to identify both proximal and distal intracranial occlusions may change this equation. In this review, we discuss the diagnosis and prognosis of mild strokes, the role of neurovascular imaging in treatment decision making, experience with thrombolysis in this patient population, and propose directions for future studies.